Akad Musyarakah dan Musyarakah Mutanaqisah (MMQ) - Dliyauddin, Dliyauddin; Caya, Rosdiyana; Basse, Rahman Ambo; Sapa, Nasrullah Bin (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Musyarakah and Musyarakah Mutanaqisah (MMQ) are two types of syirkah contracts widely used in Islamic financial institutions as interest-free financing alternatives. These contracts are based on the principles of partnership, risk-sharing, and profit-sharing. This paper analyzes the theoretical and practical aspects of both contracts, focusing on their structure, legal foundations, advantages, and implementation challenges in the context of Indonesia.